Prevalence of bradyarrhythmias needing pacing in COVID‐19. Issue 8 (19th July 2021) - Akhtar, Zaki; Leung, Lisa WM; Kontogiannis, Christos; Zuberi, Zia; Bajpai, Abhay; Sharma, Sumeet; Chen, Zhong; Beeton, Ian; Sohal, Manav; Gallagher, Mark M.
Abstract: Background: The Sars‐Cov‐2 infection is a multisystem illness that can affect the cardiovascular system. Tachyarrhythmias have been reported but the prevalence of bradyarrhythmia is unclear. Cases have been described of transient high‐degree atrioventricular (AV) block in COVID‐19 that were managed conservatively. Method: A database of all patients requiring temporary or permanent pacing in two linked cardiac centers was used to compare the number of procedures required during the first year of the pandemic compared to the corresponding period a year earlier. The database was cross‐referenced with a database of all patients testing positive for Sars‐Cov‐2 infection in both institutions to identify patients who required temporary or permanent pacing during COVID‐19. Results: The number of novel pacemaker implants was lower during the COVID‐19 pandemic than the same period the previous year (540 vs. 629, respectively), with a similar proportion of high‐degree AV block (38.3% vs. 33.2%, respectively, p = .069). Four patients with the Sars‐Cov‐2 infection had a pacemaker implanted for high‐degree AV block, two for sinus node dysfunction. Of this cohort of six patients, two succumbed to the COVID‐19 illness and one from non‐COVID sepsis. Device interrogation demonstrated a sustained pacing requirement in all cases. Conclusion: High‐degree AV block remained unaltered in prevalence during the COVID‐19 pandemic. There was no evidence of transient high‐degree AV block in patients with the Sars‐Cov‐2 infection. Our experience suggests that all clinically significant bradyarrhythmia should be treated by pacing according to usual protocols regardless of the COVID status.